Pengajaran Perkalian dan Pembagian dengan Metode Jarimatika - Husnul Khotimah; Besse Intan Permatasari; Nur Ismiyati (Abdimas Universal, 2020)
One of the subjects that requires planting concepts from an early age is mathematics. At school age, especially grade 3 students, the student's age has reached 9 to 10 years. Students at that age, among others, are happy with activity exercises and are happy with activities in the form of competitions. Based on this, learning should be packaged in the form of activities. At the elementary level, one of the materials that is the problem for students is multiplication and division. This material is basic in mathematics but it is often found that there are junior high school students who do not know the results of multiplication under 10. Jarimatika is a method for teaching addition, subtraction, multiplication and division to students, especially at the elementary level. Jarimatika is an abbreviation of finger and arithmetic. As the name implies, the media in this method are the fingers. Based on this community service activity, it can be concluded that the students are enthusiastic and happy with the teaching of multiplication and division with Jarimatika. In addition, students are motivated to answer questions from the teacher.